Data Streaming Pipelines in Life Sciences: Improving Data Integrity and Compliance in Clinical TrialS - Pramod Kumar Voola; Sowmith Daram; Aditya Mehra; Om Goel; Shubham Jain (Innovative Research Thoughts, 2023)
Data streaming pipelines have become a revolutionary tool in the field of life sciences, providing novel functionalities for managing and examining the large volumes of data produced in clinical trials. By using real-time data processing, these pipelines improve data integrity and guarantee adherence to regulatory requirements, therefore effectively tackling some of the most crucial obstacles encountered in clinical research. Preserving the integrity and precision of data is of utmost importance in clinical studies. Conventional data management systems sometimes have difficulties in keeping up with the fast flow of data from many sources, resulting in delays, discrepancies, and even problems with compliance. In order to provide continuous, real-time processing of data as it is created, data streaming pipelines offer a solution. This methodology guarantees the prompt validation, cleansing, and processing of data, therefore preserving a consistent degree of precision and minimising the likelihood of mistakes. An inherent advantage of data streaming pipelines is their capacity to manage fast-moving data streams originating from diverse sources, including electronic health records (EHRs), wearable devices, and laboratory equipment. Through the integration of multiple data sources into a cohesive pipeline, researchers may get a holistic perspective of trial results, therefore enabling more informed decision-making and prompt interventions. The real-time characteristic of streaming pipelines also facilitates proactive monitoring, enabling the timely identification of abnormalitie r data quality problems that may affect the results of trials.